The HIPC initiative in Bolivia - Lykke E. Andersen; Osvaldo Nina (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2000)
This paper discusses the implementation of the Heavily Indebted Poor Country (HIPC) initiative in Bolivia. It has been agreed in principle that the debt relief funds should be channeled to municipal governments in order to strengthen the ongoing decentralization process and to secure maximum poverty reduction effect. If everything goes according to plan, the HIPC initiative could have a substantial effect on poverty in Bolivia. However, the entire project builds on some very optimistic assumptions regarding the performance of the Bolivian economy during the next 18 years. If these optimistic assumptions do not hold Bolvivia will not reach the target debt/export ratio of 150. Even worse, if economic perfomance does not live up to expectations, there may be half-finished investment projects (roads, schools, hospitals, etc.), which cannot be completed and maintained, because the central government won't be able to deliver the funds that the donors have committed them to deliver to the municipalities.
Keywords: 330